DERADIKALISASI ISLAM (IMPLEMENTASI NILAI-NILAI PANCASILA DALAM AL-QUR’AN) - Musa Al Kadzim (An-natiq Jurnal Kajian Islam Interdisipliner, 2021)
Islam is a religion that upholds peace. However, all of this becomes a dilemma and problematic when extremist groups carry out their actions in the name of religion. This study intends to answer the question of how to reduce the level of religious-based radicalism in Indonesia. This research is a literature study, namely research that is focused on research based on references to the deradicalization of Islam. The method used is a descriptive analysis method with content analysis techniques. The results of this study are the values contained in the verses of the Qur'an about Pancasila are in harmony and support each other, so that every Muslim must be upheld in order to become a Wasathan Ummatan and not be trapped in Islamic radicalism.